Nurses’ experiences in voluntary error reporting: An integrative literature review - Woo, Jeffrey Ming Wei; Avery, Mark (Elsevier, 2021)
Objective This integrative review aimed to examine and understand nurses’ experiences of voluntary error reporting (VER) and elucidate factors underlying their decision to engage in VER.